Resolution in Support of Ethnic Studies Council Curricular and Budgetary Purview - Karina Chavarria:::Co-Chair of Ethnic Studies Council:::; Jennie Luna:::Co-Chair of Ethnic Studies Council:::
Purpose: To endorse the Ethnic Studies Council in working toward requirements of California Assembly Bill 1460, advancing Ethnic Studies Programs development and growth, creation of Ethnic Studies curriculum, and to direct funding mandated for the development of the above.